PENGARUH FAKTOR CORPORATE SOCIAL RESPONSIBILITY (ASPEK SOSIAL, EKONOMI, DAN LINGKUNGAN) TERHADAP CITRA PERUSAHAAN - Aryawan, Made; Rahyuda, I Ketut; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 6 No 2 (2017), 2017)
This study aims to explain the influence of social, economic, and environmental aspects of the corporate image of PT Pertamina (Persero) Fuel Terminal Sanggaran. The cornerstone of the theory used in this research is the corporate social responsibility, social aspects in corporate social responsibility, the economic aspects of corporate social responsibility, environmental aspects of corporate social responsibility, and corporate image. The samples used in this study was 104 respondents, the local community Fuel Terminal Sanggaran using purposive sampling method. Analysis technique used in this research is multiple linear regression analysis. The results of this study prove that the social aspect has a significant positive effect on the company's image in the PT. Pertamina (Persero) Fuel Terminal (TBBM). The economic aspect has significant positive effect on the image of perusahanaan at PT. Pertamina (Persero) Fuel Terminal (TBBM). Environmental aspects has significant positive effect on the image of perusahanaan at PT. Pertamina (Persero) Fuel Terminal (TBBM).
Keywords: social aspects; economic aspects; environmental aspects; the image of integration